Monetization of AI-Generated Songs for Authors’ Economic and Moral Rights Protection - Faradigma D. Zainuddin; nirwan Junus; Nurul Fazri Elfikri (Journal of Law, Human Rights, Immigration, and Corrections, 2026)
Rapid advancements in Artificial Intelligence (AI) have significantly impacted the music industry by enabling AI systems to autonomously create song compositions. This development presents critical legal challenges, particularly concerning the protection of economic and moral rights associated with AI-generated songs. The study examines whether current Copyright Law effectively addresses these issues, employing normative research methods and focusing on relevant legislation and concepts. Findings indicate considerable limitations within existing legal frameworks since the definition of a creator typically pertains to human authors. Consequently, works produced by AI are subjected to a legal gap, resulting in ambiguity regarding the safeguarding of moral and economic rights. The study advocates for regulatory reforms that would clearly define the legal status of AI-generated works, ensuring both legal certainty and fair intellectual property rights protection in the evolving digital landscape.